ПР ОФЕ СІЙ НО-ОСОБИСТІ СНИЙ ДОСВІД МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ ЯК ОСНОВИ ЙОГО ФАХОВОЇ КОМПЕТЕ НТНОСТІ - Popovich, N (Continuing Professional Education: Theory and Practice, 2019)
The article focuses of is professional-personal experience of the teacher of the music, being is considered by a basis of its professional competence. The role of readiness of the teacher to the realized professional work is certain; specificity modeling of professional work of the competitive expert is proved; the essence of professional self-realization of the future teacher of music is concretized.